The challenges and opportunities of women working in weaving cultural clothes at Bahir-Dar City, Bahirdar, Ethiopia - Tatek Getachew; Chekol Alemu; Habitamu Wudu (Discover Global Society)
Abstract Background Cultural weaving is a crucial component of the cotton industry, linking rural and urban households through traditional handcrafts and providing income for women, thereby enhancing family livelihoods. The demand for hand-woven garments is on the rise, although a study from 2003 to 2009 revealed a decrease in skill-based wage premiums and a slight wage penalty for women in the garment sector. Traditionally, men and women have collaborated in fabric production, with men handling weaving and women focusing on decoration. Ethiopia is highlighted as a prominent African country for its rich cultural clothing and diverse ethnic heritage. Method The study employed a qualitative research method with a case study design. Participants were selected through purposive and availability sampling for semi-structured interviews and focus group discussions. After reaching saturation with fourteen weavers and key informants, data were analyzed using thematic analysis. Result The study highlights that women weavers of cultural clothes face numerous challenges, including socio-cultural issues, psychological problems, and economic difficulties such as material shortages and outdated technology. Despite these obstacles, there are opportunities for improvement through institutional support, training programs, and social networking. Ultimately, these women benefit from income generation, work flexibility, skill development, and enhanced social satisfaction, positively impacting their lives and their families' livelihoods. Conclusion The study suggests that the Women, Children, and Social Affairs Office of Keeble should systematically address the challenges faced by women weavers, particularly regarding access to essential services and materials. Additionally, it calls for a shift in community attitudes to recognize weaving as a valuable profession that can improve lives rather than being viewed negatively.